Urgensi Kodifikasi Hukum Perdata Internasional (HPI) di Indonesia pada Era Digital: Kajian Yuridis-Empiris Terhadap Tantangan Lintas Negara dan Kebutuhan akan Kepastian Hukum - Hamonangan, Marcellius Kirana; Lie, Gunardi (Journal of Multidisciplinary Issues, 2025)
ABSTRACT Objective This study investigates the urgency of codifying Private International Law (PIL) in Indonesia as a strategic legal response to the rapid expansion of cross-border private legal interactions in the digital era. The research asks: What legal codification model can best address jurisdictional conflicts and legal uncertainties arising from transnational digital activities? Methodology Using a juridical-empirical approach, the study combines doctrinal analysis with comparative legal research. The analysis is supported by theoretical frameworks including social systems theory, responsive law, legal politics, and digital regulatory theory. Comparative evaluation is conducted across six countries—Germany, Japan, the Netherlands, Singapore, the UK, and Australia. Findings The research reveals that Indonesia’s current legal system lacks a coherent, codified framework for PIL. Legal uncertainty arises in handling transnational disputes, cross-border data breaches, and enforcement of foreign judgments. By contrast, civil and common law countries have adopted codified or flexible jurisprudential approaches to ensure clarity and adaptability. The study finds that Indonesia urgently needs a hybrid PIL codification model to align with the digital and global legal ecosystem. Novelty This study is among the first to position the codification of PIL as a legal-political and technological imperative, rather than a purely doctrinal concern. Its interdisciplinary framework integrates comparative insights and theories of digital law, offering a contextual roadmap for national legal reform. It proposes an adaptive hybrid codification model responsive to cross-border digital disputes and legal sovereignty concerns. Keywords: Private International Law; Conflict of Laws; Digital Jurisdiction; Legal Codification; Transnational Legal Protection